ANALISIS ALOKASI BIAYA BERSAMA UNTUK PENENTUAN BIAYA PRODUKSI NUTELLA CHEESE CUPCAKE DAN COOKIES CUPCAKE PADA SHMILY CUPCAKES SAMRAT MANADO - Tumbol, Olivia A.; Tinangon, Jantje; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2014)
Guidance of in the company needs to improve its business processes so that the appropriate production produced products can compete in the market . One such effort is to utilize one or several main raw material to produce two or more types of products are almost the same but with different variations to accurately allocate costs to each product so as to maximize profits.To allocate these costs accurately on each product is the relative sales value method . Where the data used is primary data obtained directly from the company. The data used in the form of selling price , direct labor costs , raw material costs , plant operating costs and marketing costs .From the analysis conducted through joint cost allocation calculation using the relative sales value method can be seen that the results obtained from the calculation of the cost allocation with the Cupcake Shmily using the relative sales value method of cost allocation obtained with Nutella Cheese Cupcake for Rp 56 723 and Cookies Cupcake for Rp . 60 108 of the total cost of Rp116.716 shared, derived from raw material costs, direct labor costs and factory overhead costs.